APLICATION OF ABC METHOD FROM AN OPERATOR OF WATER AND SEWERAGE - FÜLÖP ÁRPÁD-ZOLTÁN; BAKÓ KINGA-ERZSÉBET (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2016)
At the time of the appearance of the ABC method, many specialists considered that they found the most opportune method of calculation to allocate the overhead costs on the cost objects, otherwise said to be able to calculate the total cost of a product or service. Because the method is based on determining the total cost, we can consider that the ABC method is not a method of costing, but rather a method of cost management. Unfortunately, in the specialized literature of Roumania there are many approaches which consider that the ABC method is a method of costing in the traditional way, although in our opinion it is not. Application of ABC method to a regional operator of water and sewerage shows us the possibilities of the method, the possibilities that are offered in the field of cost and administration overhead management, respectively of the establishment of the accounting result on the different cost objects. In case of the regional operator the calculation object is the city or township in which provides the services of water and sewage.